Legal Protection for Victims of Deepfake Pornography in Terms of Criminal Law - Alfathoni, Muhammad Ilham; Pratama, Bagas Akbar; Lubis, Cherilla Izzata Putri (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2024)
The rapid development of artificial intelligence, especially through deepfake technology, has led to serious concerns, particularly when misused for pornographic purposes. Deepfake allows realistic manipulation of images and videos, often without the knowledge or consent of the depicted individual. This article explores the legal protection available to victims of deepfake pornography under Indonesian criminal law. Using a normative juridical approach with a statute and conceptual approach, the study finds that existing legal frameworks, such as the ITE Law, the Pornography Law, the Personal Data Protection Law, and the Criminal Code, are insufficient to address the unique challenges posed by deepfakes. Legal gaps and lack of explicit regulation hinder effective law enforcement and victim protection. Therefore, this paper advocates for urgent legal reforms to define and criminalize deepfake pornography explicitly and comprehensively.